CD177 Enhances the Detection of Myelodysplastic Syndrome by Flow Cytometry. Issue 4 (3rd February 2020) - Alayed, Khaled; Meyerson, Jeremy B; Osei, Ebenezer S; Blidaru, Georgeta; Schlegelmilch, June; Johnson, Michael; Meyerson, Howard J
Abstract: Objectives: Previously we demonstrated that a decreased percentage of CD177-positive granulocytes detected by flow cytometry (FCM) was associated with myelodysplastic syndrome (MDS). Here we expand on those findings to more rigorously evaluate the utility of CD177 for the detection of MDS. Methods: Two hundred patient samples (100 MDS and 100 controls) were evaluated for granulocyte expression of CD177 and 11 other flow cytometric parameters known to be associated with MDS. Results: We show that CD177, as a single analyte, is highly correlated with MDS with a receiver operating characteristic area under curve value of 0.8. CD177 expression below 30% demonstrated a sensitivity of 51% and a specificity of 94% for detecting MDS with a positive predictive value of 89.5%. In multivariate analysis of 12 MDS-associated FCM metrics, CD177 and the Ogata parameters were significant indicators of MDS, and CD177 increased sensitivity of the Ogata score by 16% (63%-79%) for predicting MDS. Finally, diagnostic criteria incorporating these parameters with a 1% blast cutoff level and CD177 resulted in a sensitivity of 90% and specificity of 91% for detecting MDS. Conclusions: The findings indicate CD177 is a useful FCM marker for MDS.